The Influence of Destination Image and Service Quality on Tourists Satisfaction - Devy Widya Apriandi; Wiwin Winengsih (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2025)
This research aims to analyze the influence of Destination Image and Service Quality on Tourists Satisfaction at the Farm House Lembang tourist destination. This research uses a quantitative approach by collecting data through questionnaires distributed to 100 tourists who have visited the destination. The data obtained was analyzed using multiple linear regression techniques to evaluate the relationship between the variables studied. The research results show that a positive destination image and high service quality significantly contribute to tourist satisfaction at Farm House Lembang. These findings indicate that destination managers need to focus on improving image and service quality to create satisfying experiences for tourists. This research provides important insights for the development of more effective destination marketing and management strategies, and suggests the need to conduct further research to explore other factors that influence tourist decisions.